Daya Tarik Eiger: Kombinasi Display Menawan dan Pelayanan Berkualitas Membuat Konsumen Ingin Kembali Lagi - Irsyad Razan Halim; Mangifera, Liana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Research is essential to understanding the influence of brand image, store image, and perceived quality on consumers' repurchase intentions, with perceived value as a mediating variable. A quantitative approach was employed using a survey with structured questionnaires administered to 140 respondents in Surakarta who had previously purchased Eiger products from offline stores. The data were analyzed using the SmartPLS method, including validity and reliability testing, as well as structural model analysis. The research revealed that consumers' repurchase intentions are significantly influenced by positive perceptions of brand image, store image, perceived quality, and perceived value. Moreover, perceived value acts as a mediator that strengthens the relationships between these factors and repurchase intentions. These findings highlight the importance of focusing on brand image, store image, and product quality to encourage increased consumer repurchase intentions. This study is limited to the geographical scope and offline stores; therefore, future research is recommended to expand the geographical coverage and consider other factors, such as price and promotions.